1987
DOI: 10.1177/004051758705700708
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Growth Period on Neps in Cotton

Abstract: The interactions between picking dates, locations, and varieties were studied to evaluate the effect of growth period on neps in ginned lint, yarn, and fabric. Five harvest intervals were selected, and the cotton yield increments between intervals were used to provide five levels of maturity. Neps in raw cotton were measured by the USDA-AMS web nep test and microscopic examination of card web, imperfections in the yarn ascertained by the Uster instrument, and neps in woven fabric counted by dyeing procedures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…More neps (in cotton with no lint cleaning) and immature cotton was associated with earlier harvest aid treatments across all experiments (Table 4). The number of neps was negatively correlated with linear density ( r = −0.83), maturity ratio ( r = −0.63), and micronaire ( r = −0.74) indicating that production of immature or low linear density fiber was most likely the reason for increased neps (Anthony et al, 1988; Dever and Gannaway, 1988; Hebert et al, 1988; Mangialardi et al, 1987). Upland cotton fiber with maturity ratios < 0.85 or a micronaire‐value <3.5 are generally considered immature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More neps (in cotton with no lint cleaning) and immature cotton was associated with earlier harvest aid treatments across all experiments (Table 4). The number of neps was negatively correlated with linear density ( r = −0.83), maturity ratio ( r = −0.63), and micronaire ( r = −0.74) indicating that production of immature or low linear density fiber was most likely the reason for increased neps (Anthony et al, 1988; Dever and Gannaway, 1988; Hebert et al, 1988; Mangialardi et al, 1987). Upland cotton fiber with maturity ratios < 0.85 or a micronaire‐value <3.5 are generally considered immature.…”
Section: Resultsmentioning
confidence: 99%
“…Immature fiber and neps even in small amounts are undesirable (Ethridge and Simonton, 2004) as they decrease mill processing efficiency and ruin the appearance of finished yarns and fabrics. Immature fibers and neps absorb less dye and reflect light differently, and consequently appear as under‐dyed barred patterns and/or “flecks” on finished fabrics (Bradow et al, 1996; Goynes et al, 1997; Mangialardi et al, 1987). Rarely are there direct penalties for growers when there is high incidence of neps, their presence can however, affect overall the sources reputation when cotton arrives at spinning mills (Gordon et al, 2004).…”
mentioning
confidence: 99%
“…Therefore, the uniformity index and length decrease in immature fibers and the neps ratio increases. Mangialardi et al (1987) reported that less defective yarn and fabric in terms of neps will be produced from cotton obtained at the beginning of the harvest season compared to cotton obtained at the end of the harvest season in the same field. The neps not only affect the appearance of cotton yarns and fabric, but also often lead to lower yarn strength, spinning ends down and low uniform yarn production (Van der Sluij and Hunter 2016).…”
Section: Neps+200(%)mentioning
confidence: 99%
“…The presence of the sub-microscopic system of capillaries in the cellulose fibers is of paramount significance, because it is the channel of chemical reactions by which water-soluble reagents penetrate deep in the cellulose structure. More active hydroxyl groups interacting with various substances are also disposed here [15][16][17][18].…”
Section: Cotton Fiber Biodamagingmentioning
confidence: 99%
“…Damaging of cotton fibers, fabrics and textile products by microorganisms is primarily accompanied by occurrence of colored yellow, orange, red, violet, etc. spots and then by putrefactive odor, and, finally, the product loses strength and degrades [18][19][20][21][22][23].…”
Section: Cotton Fiber Biodamagingmentioning
confidence: 99%